2001
DOI: 10.1038/sj.bjp.0704142
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus, but not the structurally related RAD (everolimus), enhances the negative effects of cyclosporine on mitochondrial metabolism in the rat brain

Abstract: 1 Clinical studies have shown enhancement of cyclosporine toxicity when co-administered with the immunosuppressant sirolimus. We evaluated the biochemical mechanisms underlying the sirolimus/ cyclosporine interaction on rat brain metabolism using magnetic resonance spectroscopy (MRS) and compared the e ects of sirolimus with those of the structurally related RAD. 2 Two-week-old rats (25 g) were allocated to the following treatment groups (all n=6): I. control, II. cyclosporine (10 mg kg 71 d 71 ), III. sirolim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 35 publications
10
82
1
3
Order By: Relevance
“…Thus, we concluded that the ability of rapamycin to inhibit mTOR activity might be impaired after prolonged huntingtin expression or increased aggregate formation 8 . Therefore, early treatment with rapamycin may attenuate Huntington disease in vivo, as rapamycin (and its analogs) are lipophilic, show good blood-brain barrier penetration [11][12][13][14] and are designed for long-term use in humans 11 .…”
mentioning
confidence: 99%
“…Thus, we concluded that the ability of rapamycin to inhibit mTOR activity might be impaired after prolonged huntingtin expression or increased aggregate formation 8 . Therefore, early treatment with rapamycin may attenuate Huntington disease in vivo, as rapamycin (and its analogs) are lipophilic, show good blood-brain barrier penetration [11][12][13][14] and are designed for long-term use in humans 11 .…”
mentioning
confidence: 99%
“…Rats were treated with 10 mg/kg per day CyA or a vehicle solution (n = 5 each) for a period of 6 days in order to establish constant drug tissue levels. This oral dose was chosen on the basis of our previous dose-funding studies for the brain [20] and heart [12]. During the study period, the animals were closely monitored, including daily evaluations of appearance, grooming, appetite, behavior, activity, and body weight.…”
Section: Animalsmentioning
confidence: 99%
“…For MRS, we extracted the collected frozen tissue samples using a dual perchloric acid (PCA)/lipid extraction procedure [20]. The powdered frozen tissue was added to 6 ml of ice-cold 12% PCA for protein precipitation and subsequently homogenized using electrical homogenizer.…”
Section: Dual Extraction Of Rat Tissuesmentioning
confidence: 99%
“…Brain tissue was highly resistant to inhibition by CsA because physiological barriers, such as the blood-brain barrier (BBB), and the abundance of CsA-binding proteins, such as immunophilins, determined the degree to which CsA accumulated in each tissue in vivo. CsA was primarily taken up from lipoprotein at the blood-brain interface, but because of the tight junctions at the blood-brain and blood-CSF barriers, CsA effectively became trapped in cerebral endothelial cells and the choroid plexus (22). In addition, Dohgu et al (23) investigated the mechanism by which CsA causes BBB dysfunction in rodent brain endothelial cells.…”
Section: Discussionmentioning
confidence: 99%